USE OF FOREIGN EXPERIENCE IN THE EDUCATION SYSTEM AND FEATURES OF EDUCATIONAL TECHNOLOGIES (Scientific journal of the Fergana State University, 2024)
The article briefly analyzes the structure, experience and modern educational programs of advanced foreign educational systems such as Japan, Germany, France, and the USA. Also, the unique aspects of technologies in the educational system are recognized.